#TITLE_ALTERNATIVE# - PRIMANDA (NIM : 13205039); Pembimbing : Ir. Sigit Haryadi, MT, GALIH
Leased line is one factor for network providers and telecommunications services is a fee charged to users by using network rental services provided by the organizer and collected a period in accordance with the agreed contract. This final project will compare to simulation in order to calculate the leased line service Cost for telecommunication provider in case of non-sharing BTS and sharing BTS (active infrastructure sharing for microwave) between any other telecommunication provider. One of the methodes that use to calculate the rate in basis of leased line service Cost is Forward Looking Long Run Incremental Cost-Plus (FLLRIC+) with Bottom-Up approach. This calculation is based on distance, kind od user, and capacity. The experience result show that the efficiency in Capital Expanditure as the input parameter in costing the leased line rate by using BTS sharing method can lowering the leased line rate. The Capex efficiency for local transmission is about 58,02% and Long Distance transmission is about 40,39%, where that efficiency can lowering the leased line rate for local transmission is about 30% and for Long Distance transmission is about 5 to 35% depend on transmission distance.